Improved Global Navigation Satellite System filtering methods for the mobile six-minute walk test - Ogris Maximilian; Edegger Kurt; Rzepka Angelika; Ziegl Andreas; Schreier Günter (Current Directions in Biomedical Engineering, 2022)
Heart failure (HF) is a chronic disease with high hospitalizations rates and increased mortality. The six-minute walk test (6MWT) is a standardized method to assess the functional health of HF patients by measuring the distance walked in six minutes [1]. The improved 6MWT with new filter algorithms, based on the development of smartphone application [9], can be used everywhere with a good global navigation satellite system (GNSS) signal. This paper tests multiple filtering approaches to reduce the measured distance error in the application.We were able to decrease the average relative error of the application from 4.5% to 2.0%. Additionally, the number of experiments with relative error over our chosen clinically significant difference of 5% is reduced by 90%. Keeping these results in mind, the system can be considered clinically acceptable.